1999
DOI: 10.1086/514738
|View full text |Cite
|
Sign up to set email alerts
|

Conventional Respiratory Viruses Recovered from Immunocompromised Patients: Clinical Considerations

Abstract: Lower respiratory tract infection is the most common complication in the immunocompromised patient. From January 1991 to December 1995, 785 consecutive patients with suspected respiratory tract infections were studied. One hundred ninety-nine viruses were isolated from 182 (23%) of 785 bronchoalveolar lavage fluid specimens. Cytomegalovirus was isolated from 131 patients, herpes simplex virus was recovered from 31, and conventional respiratory viruses (CRVs) were recovered from 36. There were 9 influenza A vir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
31
1
5

Year Published

2001
2001
2013
2013

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(40 citation statements)
references
References 18 publications
3
31
1
5
Order By: Relevance
“…The severity of respiratory viral disease in our patients with cancer is in concordance with other studies that have documented a high frequency of pneumonia and death associated with respiratory viral infections in persons with cancer and hematologic malignancies. 1,3,13,24 In our study, 2 (7%) oncology patients with RSV infection died. Both children had severe neutropenia (60 and 100 neutrophils/mm 3 ) when they acquired the viral infection.…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…The severity of respiratory viral disease in our patients with cancer is in concordance with other studies that have documented a high frequency of pneumonia and death associated with respiratory viral infections in persons with cancer and hematologic malignancies. 1,3,13,24 In our study, 2 (7%) oncology patients with RSV infection died. Both children had severe neutropenia (60 and 100 neutrophils/mm 3 ) when they acquired the viral infection.…”
Section: Discussionmentioning
confidence: 47%
“…In healthy children these viruses usually cause upper respiratory tract infections, with a self-limited and benign course. However, they can lead to severe disease, with significant morbidity and mortality, in immunocompromised patients, [1][2][3][4] especially in the setting of myelosuppression 5 and/or hematopoietic stem cell transplant (HSCT). [5][6][7][8] Several studies in adults have shown that common respiratory virus infections progress to lower respiratory tract disease and pneumonia in up to 30% to 50% of immunosuppressed HSCT recipients.…”
mentioning
confidence: 99%
“…Although the viruses tested for in the present study have previously been reported to be significant pathogens, especially in immunocompromised bone marrow and lung transplant recipients (24,29), the patient population in our study was not specifically targeted to assess the incidence of these infections through a winter period. Future work would aim at a more targeted population.…”
Section: Discussionmentioning
confidence: 99%
“…However, they may also be associated with more-severe lower respiratory tract infections in children, in the elderly (23,24,30,33), and in immunocompromised patients (14,39,48,49). RVs have been isolated from cases of cystic fibrosis (44), otitis media (3), sinusitis (37), and exacerbations of chronic bronchitis and asthma (12,21,22,34).…”
mentioning
confidence: 99%